Maternal and child dietary intake: The role of maternal healthy-eater self-schema. (1st June 2018) - Kueppers, Julie; Stein, Karen Farchaus; Groth, Susan; Fernandez, I. Diana
Abstract: Background: Mothers play a key role in shaping the dietary intake of their young children through their own dietary intake and the foods they make available at home. Therefore, understanding the mechanisms underlying maternal food choices is crucial. Cognitions about the self as a healthy eater, referred to as healthy-eater self-schema (HESS), predict dietary intake in diverse samples, but the linkage has not been investigated in mothers and their feeding behaviors. This study examined the relationship between a maternal HESS, maternal and child intake of fruits, vegetables, saturated fat, and added sugar, and home food availability. Methods: A cross-sectional, descriptive design was used with mothers and their 2–5 year old children (N = 124 dyads). Kendzierski's Healthy-Eater Self-Schema questionnaire was used to measure HESS. Block Food Frequency Screeners were used to measure diets (mother and child) and the Home Environment Survey was used to measure home availability of fruits/vegetables and fats/sweets. Multiple regression and multiple mediation analyses were performed. Results: Maternal HESS was positively associated with maternal intake of fruits and vegetables, and negatively associated with intake of added sugar. Maternal HESS was not directly associated with child dietary intake, but was indirectly associated with child intake of fruits, vegetables, and added sugar through maternal intake of the same foods. Home food availability was not significantly associated with HESS. Conclusion: This study found that a mother's HESS was positively associated with her diet, which was subsequently associated with aspects of her child's diet. Interventions to foster development of HESS in mothers may be an effective means to promote healthy dietary intake in mothers and their young children.